Evaluation of Flexural Strength and Microhardness of Different Type Glass Ionomer Cements - Bilge, Kübra; Aşar, Enes Mustafa; Ipek, Irem (My University, 2024)
Abstract Purpose: The aim of this study is to evaluate and compare flexural strength and microhardness of different types of glass ionomer cements (Fuji IX GP® Fast, Riva LC HV, EQUIA Forte Fil). Materials and Methods: A total of 30 samples (n = 10) were prepared for microhardness test, and an additional total of 30 samples (n = 10) were prepared for the flexural strength test. Customized stainless steel molds (25×2×2 mm³) were produced for the flexural strength test, and 10 mm and 2 mm plexiglass molds were produced for the microhardness test. The prepared samples were stored in distilled water in a dark bottle at 37 °C (±1 °C) for 24 hours. A three-point bending test was performed using a universal testing device, and the maximum force values required to fracture the samples were determined in Newton by the device after the fracture. For the Vickers microhardness test measurements were made from different areas of the upper surfaces of each sample and the average of five measurements was calculated in MPa. Results: When comparing the flexural strength values, EQUIA Forte Fil group observed the highest flexural strength value, while Riva LC HV group had lowest flexural strength value. When comparing the microhardness values, EQUIA Forte Fil group showed the highest microhardness value, whereas Riva LC HV group observed the lowest microhardness value. Conclusion: The use of EQUIA Forte Fil, which has the highest microhardness and flexural strength values, and similarly strengthened glass ionomer cements may enhance clinical success. Key Words: glass ionomer cements; microhardness; flexural strength
Keywords: Flexural strength; microhardness; glass ionomer cements